Identifying research waste from surgical research: a protocol for assessing compliance with the IDEAL framework and recommendations - Xin Sun; Peter McCulloch; Allison Hirst; Youping Li; Jiajie Yu; Fei Shan (BMJ Surgery, Interventions, & Health Technologies, 2021)
Introduction Approximately £1130 billion was invested in research worldwide in 2016, and 9.6% of this was on biomedical research. However, about 85% of biomedical research investment is wasted. The Lancet published a series to identify five categories relating to research waste and in 2014. Some categories of research waste in surgery are avoidable by complying with the Idea, Development, Exploration, Assessment, Long-term follow-up (IDEAL) framework for it enables researchers to design, conduct and report surgical studies robustly and transparently. This review aims to examine the extent to which surgical studies adhered to the IDEAL framework and estimate the amount of overall research waste that could be avoided if compliance was improved.Methods We will search for potential studies published in English and between 1 January 2018 and 31 December 2018 via PubMed. Teams of paired reviewers will screen titles, abstracts and full texts independently. Two researchers will extract data from each paper. Data will be collected about general information and specialised information in each stage, and our IDEAL Compliance Appraisal tool will be used to analyse included studies. Descriptive statistics and χ2 or Fisher’s exact tests for comparisons will be presented.Discussion Our study will provide important information about whether compliance with the specific IDEAL Recommendations has reduced research waste in surgical and therapeutic device studies. And we will identify particular key aspects that are worse and need to focus on improving those in future education.